Drafting distance in swimming - Chatard, J. C.; Wilson, B. (Medicine & Science in Sports & Exercise, 2003)
PURPOSE: This study investigates the effect of the distance separating the lead and draft swimmers on the metabolic and hydrodynamic responses of the draft swimmer. METHODS: A nondrafting swim of 4 min at 95% of the best 1500-m pace for 11 swimmers was compared with swimming in a drafting position at four different distances directly behind another swimmer (0, 50, 100, and 150 cm). Swimming performance was assessed by stroke rate and stroke length; the metabolic response by oxygen uptake, heart rate, and blood lactate; and the rating of perceived exertion by the Borg scale. Passive drag was assessed at these drafting distances by passive towing. Then, passive drag was measured in six swimmers towed in six lateral drafting positions, with swimmers separated by approximately 40 cm, and then measured in two positions at the rear of the lead swimmer with a reduced lateral distance between swimmers of 50 and 0 cm. RESULTS: Oxygen uptake, heart rate, blood lactate, rating of perceived exertion, and stroke rate were significantly reduced and stroke length was significantly increased in all drafting positions compared with the nondrafting position. For drag, the most advantageous drafting distances were 0 and 50 cm back from the toes of the lead swimmer. Drag was reduced by 21% and 20%, respectively. In lateral drafting, drag was significantly reduced by 6% and 7%, respectively, at 50 and 100 cm back from the hands of the lead swimmer. CONCLUSIONS: Swimming behind another swimmer at a distance between 0 and 50 cm back from the toes was the most advantageous, whereas in lateral drafting the optimal distance was 50-100 cm back from the hands of the lead swimmer.